Investigating Undergraduate Students’ Experiences with Argumentative Writing in a Post-War Kosovo - Mustafa, Blerta (Journal of Academic Writing, 2011)
This action research study reports on Kosovan, English as a Foreign Language, undergraduate students’ perceptions of the usefulness and effectiveness of class activities that promote the panning for gold approach (Browne and Keeley 2004) in the process of argumentative writing. The data obtained from a questionnaire, essay evaluation and a focus group, reveal that students show interest in the approach though they do not feel at ease when required to take a decision that calls for systematic evaluation of their thinking in a quest for new answers. It is apparent from the study that, in order for students to think critically and write argumentatively, the panning for gold approach and the principle of inquiry should be integrated across the curriculum or, in a better case scenario, should be an integrated part of daily life. The results have implications for syllabus and classroom practices.